Analisis Penerapan Hygiene Sanitasi pada Penyelenggaraan Makanan di Rumah Sakit Umum Daerah Konawe Kepulauan - Fajarwati, Novita; Abadi, Ellyani; Ihsan M, Habib; Demmalewa, Jenny Qlifianti; Dhesa, Desiderius Bela; Ananda, Siti Hadrayanti; Fatmawati, Fatmawati (Jurnal Gizi Ilmiah, 2023)
Organizing food according to the principles of hygiene and sanitation can prolong the treatment process and cause cross infections or nosocomial infections (infections acquired in hospitals). The aim of this research is to analyze the application of sanitation hygiene in food handling. This type of research is quantitative with a descriptive survey design. This research was conducted at the Konawe Islands Regional General Hospital in August 2023. The sample was all 9 employees working at the nutrition installation in 2023. The sampling technique uses the total sample. Data was obtained using a questionnaire and observed. Descriptive data analysis. The research results showed that the implementation of handler hygiene was found in 44.6% of samples not using gloves and 22.2% of samples using jewelry. The application of sanitation in food processing places is not provided for food processing places (kitchens) in accordance with construction, layout, building and kitchen room requirements and smoke does not come out through chimneys and is not equipped with smoke hoods and sanitary cooking equipment has surface layers of equipment that do not dissolve in acid. Bases or salts commonly found in food and cooking utensils such as cutting boards and knives are not differentiated between raw food and ready-to-eat food.